SEVERITY OF MOBILE PHONE AND INTERNET USE AMONG B.SC. NURSING STUDENTS - Kumari, Arpita; D'souza, Melita Shiny; Dhar, Thiangmon; Savitha; Alex, Soumya (Journal of Health and Allied Sciences NU, 2013)
Introduction: India continues to be one of the fastest growing major telecom markets in the world. Around 60 million of internet users are from India and 19 to 40 years age group section 85% using internet in India. Young nurses today have wide spread and inexpensive access to the internet.Aims and Objectives: To assess the severity score of mobile phone use and internet use among BSc. Nursing students and to find the relationship between mobile phone and internet use.Study design: descriptive survey.Methods and materials: The study was conducted among 114 BSc. nursing students in Manipal College of nursing Manipal. A convenient sampling technique was used. The data was obtained by using a demographic proforma, mobile phone addiction test and internet addiction test.Results: Most of the subjects 50 (43.9%) belongs to 19-20 years of age. 1.8% subjects reported of having mild addiction to mobile phone use. Three (2.6%) subjects had moderate internet addiction and 35 (30.7%) subjects reported of having mild internet addiction. The 'r' value (r=0.610, p=≤0.001) showed that there is a positive relationship between use of mobile phone and internet use.
Keywords: Mobile phone use; internet use; severity score; B.Sc. Nursing students